Overcoming paradigms in criminology and their consequences for criminal dogma (Revista do Tribunal Regional Federal da 3ª Região, 2012)
Do the new values of Criminology surpass its old paradigms? Have we found new paradigms for Criminology today? What is their influence on penal dogmatics? This essay will try to address these questions in the light of the changing focus of Criminology, its new line of approach and method of study, in an incomplete attempt - given the limits and purposes of this work - to outline its direction and contribution as a science, and thus try to point out its reflections on criminal policy and contemporary criminal dogma, in comparison with its obstacles and challenges. Certainly, given the broad historical and scientific panorama of the subject, these lines will only touch on a few of the master ideas that have founded the scientific thought of the last century and their influences, given the vast field of speculation and theoretical nuances that have fostered the evolution of the study in question; the intricate interaction of criminology with criminal dogmatics, its conflicts and challenges. The work therefore seeks only a critical reflection of these paradigms in order to point out the evolutionary path of science, the debates and ideas that have passed through, as well as highlighting those that still prevail in criminal science in the contemporary world - because the merit of the work is precisely to shed light on this utilitarian pragmatic analysis of the studies. To this end, an interdisciplinary analysis of the interaction between these branches of science is sought, in a macro and partial quadrant, given the inevitable difficulties in covering in a few pages the effervescence of this approach, which is still incomplete and full of challenges for the science itself.
Keywords: criminal dogmatics; criminology; paradigms; overcoming; social character of crime; social reaction